The level of understanding on balanced scorecard at Human Resource Management Unit of Chief Minister Department / Muhammad Arif Hamli - Hamli, Muhammad Arif (Universiti Teknologi MARA, Sarawak, 2013)
In this chapter, I will discuss regarding on the organization that I had my practical training. Other than that, I will also discuss regarding the department and section which I am attached to. ln the early days, the state civil service is divided into 2 sections that are the Secretariat and District. In the year 1997, the Secretariat is considered as central administrative and led by two Europeans and was assisted by a Malay clerk, three Chinese clerk and 3 office assistors. During the formation of Malaysia there is 2,599 staff and the numbers kept increasing to the total of 14,295 people in the year 2011. In 1966, main secretariat office was transferred to the Bangunan Secretariat in front of Padang Sentral, Kuching which before is situated at Resident and District Office. Then the secretariat was changed into Pejabat Perjawatan Negeri on the year 1976 and then it was moved again to Wisma Bapa Malaysia in the same year. Due to reformation State Government State Office on 1st November 1995, the 'Pejabat Penjawatan Negeri' is known as Bahagian Pengurusan Sumber Manusia'. A Director was appointed to lead the section and is responsible to State Government Deputy Secretary (Human Resource). On 25th August 2001, the,section was known as 'Human Resources Management Unit (HRMU)' thanks to reformation of organizational structure of the Chief Minister Department. The office of Human Resources Management Unit is still at Wisma Bapa Malaysia. The Human Resources Management Unit is further divided inte 8 sections which is Organizational Development Section, Recruitment section, Career section, Shared Service Section, Benefit Section, Informatioan Section, Training Section, and Discipline Section. Each of these sections is led by one Ketua Penolong Pengarah (KPP) which is responsible to run the functions of Human Resource Management Unit to achieve the mission, vision and objective that had been set.